Aportes de la teoría psicoanalítica para la comprensión de las adicciones. (2018)
The following article contributes to the understanding of the problem of addictions from a psychoanalytic point of view. The different theoretical positions of Freudian, Lacanian and other psychoanalytic schools were reviewed in order to answer the following research questions: How are addictions understood from a psychoanalytic point of view? How – from Lacanian and Freudian theory – is the understanding of addiction addressed? What do other schools of psychoanalysis state about this problem? It is found that it is a field of constant publication in the psychoanalytic literature that it is an increasing clinical phenomenon and that continuous investigation is required in this field.